2023
DOI: 10.3390/genes14030718
|View full text |Cite
|
Sign up to set email alerts
|

Association of NEF2L2 Rs35652124 Polymorphism with Nrf2 Induction and Genotoxic Stress Biomarkers in Autism

Abstract: Increased oxidative/genotoxic stress is known to impact the pathophysiology of ASD (autism spectrum disorder). Clinical studies, however, reported limited, heterogeneous but promising responses to treatment with antioxidant remedies. We determined whether the functional polymorphism of the Nrf2 gene, master regulator of anti-oxidant adaptive reactions to genotoxic stress, links to the genotoxic stress responses and to an in vitro effect of a NRF2 inductor in ASD children. Oxidative stress biomarkers, adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…Subasi Turgat et al [250] found that ASD patients had lower levels of Nrf2 and higher levels of Keap1 than normal controls, suggesting but not proving that lowered Nrf2 may have a role in ASD causation. Such causation is also suggested by the Porokhovnik et al [251] study, in which there were no significant differences shown in autism incidence in patients carrying a genetic polymorphism in the Nrf2 gene compared to those carrying the more common Nrf2 gene, but some significant differences in oxidative DNA effects and another stress response in ASD patients were shown. That study, although an interesting one, may be limited because of its insufficient size.…”
Section: Rhoamentioning
confidence: 57%
“…Subasi Turgat et al [250] found that ASD patients had lower levels of Nrf2 and higher levels of Keap1 than normal controls, suggesting but not proving that lowered Nrf2 may have a role in ASD causation. Such causation is also suggested by the Porokhovnik et al [251] study, in which there were no significant differences shown in autism incidence in patients carrying a genetic polymorphism in the Nrf2 gene compared to those carrying the more common Nrf2 gene, but some significant differences in oxidative DNA effects and another stress response in ASD patients were shown. That study, although an interesting one, may be limited because of its insufficient size.…”
Section: Rhoamentioning
confidence: 57%
“…Moreover, high levels of nitrosative stress biomarkers and NO synthase inhibitors were found to induce changes of behavioral ASD-associated phenotype [53]. Analogous increases of oxidative stress were found to induce a polymorphism of the NRF2 gene, which is a master regulator of antioxidant stress [54]. Additional known stresses were found effective in the expression of ASD genes [55,56].…”
Section: Mechanisms Of Asd Gene Operations: Key Role Of Synapsesmentioning
confidence: 98%
“…Существует множество гипотез развития ДА, однако в настоящее время считается, что ключевую роль в развитии ДА играет сочетание двух факторов: генетической предрасположенности и воздействия факторов окружающей среды [4][5][6]. Выделяют три физиологические и метаболические причины ДА: иммунную дисфункцию, окислительный стресс и митохондриальную дисфункцию [7][8][9][10].…”
Section: Introductionunclassified